(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2013)
The present benchmark research "Morphologically characterized spores of mycorrhizal fungi of the genus Glomus sp. at the level of greenhouse and field in the cultivation of soybean Glycine max L. " it was conducted during the months of November to February 2013 2012 on the farm of Limoncito, province of Santa Elena. The objectives of the study were: isolate and identify more efficient mycorrhizal spores morphologically, multiply the isolated spores in culture de Brachiaria decumbens., testing effectiveness of mycorrhizal fungi identified on the cultivation of soy and compare the performance of native spores of arbuscular mycorrhizal foreign selling in the local market. The experimental design of blocks completely at random, five treatments with four replications was employed. Comparisons of treatment means, were made using DUNCAN multiple range test at 5% probability. Management of the experiment was done by preparing the ground with a pass of plough and two passes of dredge.The variables evaluated were: 15, 30, 45 days and harvest plant height, height of insertion of the first fruit, number of nodules at 30 and 60 days after planting, number of spores to the 30, 60 days of growing, number of pods per plant, number of seeds per plant, weight of 100 seeds, performance expressed in kg / has.Economic analysis, (foreign Mycorrhizae Bradyrhizobium) T4 and T3 (native Bradyrhizobium Mycorrhizae) were those of higher income with respect to the witness.